Securing e-Learning Transactions using Digital Signature - Pasari, Anup; Islam, Kh Amirul; Karforma, Sunil; Mukhopadhyay, Sripati (International Journal of Computer Sciences and Engineering, 2025)
E-Learning is one of the most effective applications of Information and Communication Technology (ICT). In eLearning environment participants such as Teacher, Student and Administrator perform their transaction electronically through Internet which is inherently insecure. During transaction process intruders may manipulate the message. Digital signature may be used to detect any change caused by intruders. To ensure information authenticity, the digital signature is the most suitable replacement of hand written signature. In this paper, we have applied ElGamal Digital Signature Algorithm (ElGamal DSA) combined with Secure Hash Algorithm (SHA-256) to check the authenticity of the sender and we have also used International Data Encryption Algorithm (IDEA) to impose security of digital document during transaction between student and administrator of an e-Learning system. The proposed model accommodates security of ElGamal Digital Signature Algorithm in combination with SHA-256 as hashing technique and IDEA encryption technique. The performance of the proposed model is analyzed with the help of supporting tables and charts